A highly polarized radio jet during the 1998 outburst of the black hole transient XTE J1748-288 - Brocksopp, C.; Miller-Jones, James; Fender, R.; Stappers, B. (Wiley-Blackwell Publishing Ltd., 2007)
XTE J1748-288 is a black hole X-ray transient which went into outburst in 1998 June. The X-ray light curves showed canonical morphologies, with minor variations on the `fast rise exponential decay' profile. The radio source, however, reached an unusually high flux density of over 600 mJy. This high radio flux was accompanied by an exceptional (>20 per cent) fractional linear polarization, the variability of which was anticorrelated with the flux density. We use this variability to discuss possible depolarization mechanisms and to predict the underlying behaviour of the (unresolved) core/jet components.